2023
DOI: 10.7554/elife.82263
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of marmoset primordial germ cell-like cells using induced pluripotent stem cells

Abstract: Reconstitution of germ cell fate from pluripotent stem cells provides an opportunity to understand the molecular underpinnings of germ cell development. Here, we established robust methods for pluripotent stem cell (iPSC) culture in the common marmoset (Callithrix jacchus, cj), allowing stable propagation in an undifferentiated state. Notably, iPSCs cultured on a feeder layer in the presence of a WNT signaling inhibitor upregulated genes related to ubiquitin-dependent protein catabolic processes and enter a pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…To this end, we differentiated cjiPSCs in cjPSCM with or without ActA into pre-ME, which were then induced into cjPGCLCs. CjPGCLCs were isolated by FACS from d4 EBs after staining for the cell surface markers INTEGRINα6 (INTα6) and CXCR4 ( Fig 6A–C ), which are routinely used to sort primate PGCLCs ( Sasaki et al, 2015 ; Kojima et al, 2017 ; Mitsunaga et al, 2017 ; Sakai et al, 2020 ; Seita et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we differentiated cjiPSCs in cjPSCM with or without ActA into pre-ME, which were then induced into cjPGCLCs. CjPGCLCs were isolated by FACS from d4 EBs after staining for the cell surface markers INTEGRINα6 (INTα6) and CXCR4 ( Fig 6A–C ), which are routinely used to sort primate PGCLCs ( Sasaki et al, 2015 ; Kojima et al, 2017 ; Mitsunaga et al, 2017 ; Sakai et al, 2020 ; Seita et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…The developmental pathway of mammalian germ cells can be reconstituted in vitro. In particular, pluripotent stem cells (PSCs) such as embryonic stem cells (ESCs) or induced pluripotent stem cells (iPSCs) of rodents, primates, and other mammals can be differentiated into PGC-like cells (PGCLCs), which represent early PGCs in vivo ( Hayashi et al, 2011 ; Irie et al, 2015 ; Sasaki et al, 2015 ; Sugawa et al, 2015 ; Sosa et al, 2018 ; Overeem et al, 2023 ; Seita et al, 2023 ; Shono et al, 2023 ). Mouse PGCLCs (mPGCLCs) can even give rise to functional mature oocytes or spermatocytes in vitro when aggregated with gonadal somatic cells to generate reconstituted ovaries or testes ( Hayashi et al, 2012 ; Hikabe et al, 2016 ; Ishikura et al, 2016 , 2021 ; Yoshino et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…bPGCLCs expressed transcription factors important for PGC specification, such as BLIMP1 , TFAP2C , SOX17 , and NANOS3 [ 2 , 4 , 5 , 6 , 7 , 10 ]. In contrast, SOX2 was not expressed in the bPGCLCs ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Its value can be further enhanced by its application in humans, livestock, and endangered species, where it could eventually contribute to the treatment of infertility, improvement of animal breeding, and conservation of vulnerable species [ 1 ]. Recent reports have demonstrated that primordial germ cells (PGCs), the precursor cell population of gametes, are induced from ES/iPS cells in mammalian species including humans, monkeys, rabbits, rats, and rhinoceroses [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. However, in vitro gametogenesis remains underdeveloped for use in livestock.…”
mentioning
confidence: 99%